Effect of denaturation of DNA on the molecular organization of a fluorescent dye in ultra thin films. (2nd July 2016) - Saha, Mitu; Bhattacharjee, J.; Hussain, S. A.; Bhattacharjee, D.
ABSTRACT: Acridine Orange (AO) forms H-dimer in solid state and in ultra thin films. However, H dimer of AO reduces its efficiency as a usefull material for fluorescence probe. In the present work detailed investigations has been done on the interaction of AO with different forms of DNA in order to check the effectiveness in controlling the dimeric sites of AO in the Layer by Layer (LbL) self assembled film. It was found that single stranded DNA (ssDNA) is most effective than the dsDNA and coil-shaped DNA in controlling the dimeric sites of AO in LbL film.